Viability of autoclaved municipal solid waste as a source for biofuels and other products - Abdullah, Jwan (2016)
Energy is an important requirement for population growth, technological progress and urbanisation. Worldwide energy demand has been projected to increase by 5-fold by 2100. Fulfilment of these energy requirements cannot be solely from fossil fuels, such as oil, coal and natural gas, on account of their adverse environmental impacts and concomitant depletion of natural resources. As a result multiple approaches for generating alternative energy are being explored globally. In this study, processed municipal solid waste (MSW) fibre was assessed as a substrate for the production of various bio-energy related products. The MSW was characterised and the results showed that there was, as expected, a wide compositional variation between samples. There was a significant amount of lignocellulosic material found in some samples and the potential to exploit this to generate fermentable sugars was explored. Direct enzyme hydrolysis using 30 FPU (Filter Paper Units)/g Cellic® CTec2 gave a 30 % release of available glucose. Pre-treatments- using hot water, dilute acid and dilute alkali are all applied to enhance sugar release but were all found to be ineffective. The possibility of using MSW as a substrate for cellulase enzyme production via solid state fermentation (SSF) by Trichoderma reesei (T. reesei) and Aspergillus niger (A. niger) was explored. Both fungi grew well on the substrate and following optimization a cellulase activity of 26.10±3.09 FPU/g could be produced using T. reesei at 30 °C with a moisture content of 60 % with inoculation of 0.5 million spores/g and incubation for 168 hr. Addition of extra nitrogen and/or carbon did not improve cellulase accumulation. Acid or alkali pre-treatment of MSW led to reduced cellulase production. Crude enzymes produced from MSW by T. reesei were evaluated for their ability to release glucose from MSW. A cellulose hydrolysis yield of cellulase was 24.7 % achieved, which was close to that obtained using a commercial enzyme. Results demonstrated that MSW could be used as an inexpensive lignocellulosic material for the production of cellulase enzymes. High concentrations of toxic heavy metals were found in all MSW samples tested and this precludes the use of this material as a soil enhancer. Thus studies were undertaken to explore the potential for bioleaching as a means to generate compost that meets environmental standards for safe use. A. niger and Saccharomyces cerevisiae NCYC2592 were used and the impact of growth medium and pH tested. Both organisms were effective at solubilising the heavy metals and this may be related to their ability to synthesise organic acids into the fermentation medium that act as chelators.